Race differences in cardiovascular disease and breast cancer mortality among US women diagnosed with invasive breast cancer. (1st June 2019) - Troeschel, Alyssa N; Liu, Yuan; Collin, Lindsay J; Bradshaw, Patrick T; Ward, Kevin C; Gogineni, Keerthi; McCullough, Lauren E
Abstract: Background: Breast cancer (BC) survivors are at increased risk of cardiovascular disease (CVD) due to shared risk factors with BC and cardiotoxic treatment effects. We aim to investigate racial differences in mortality due to CVD and BC among women diagnosed with invasive BC. Methods: Data from 407 587 non-Hispanic Black (NHB) and White (NHW) women diagnosed with malignant BC (1990–2014) were obtained from the Surveillance, Epidemiology, and End Results database. Cumulative incidence of mortality due to CVD and BC was calculated by race and age (years). Cox models were used to obtain hazard ratios (HR) and 95% confidence intervals (95%CI) for the association of race/ethnicity with cause-specific mortality. Results: The 20-year cumulative incidence of CVD-related mortality was higher among younger NHBs than NHWs (e.g. age 55–69: 13.3% vs 8.9%, respectively). NHBs had higher incidence of BC-specific mortality than NHWs, regardless of age. There was a monotonic reduction in CVD-related mortality disparities with increasing age (age <55: HR = 3.71, 95%CI: 3.29, 4.19; age 55–68: HR = 2.31, 95%CI: 2.15, 2.49; age 69+: HR = 1.24, 95%CI: 1.19, 1.30). The hazard of BC-specific mortality among NHBs was approximately twice that of NHWs (e.g. age <55: HR = 1.98, 95%CI: 1.92, 2.04). Conclusions: There are substantial differences in mortality due to CVD and BC between NHB and NHW women diagnosed with invasive BC. Racial differences were greatest among younger women for CVD-related mortality and similar across age groups for BC-specific mortality. Future studies should identify pathways through which race/ethnicity affects cause-specific mortality, to inform efforts towards reducing disparities.